2020
DOI: 10.1038/s41598-020-60289-8
|View full text |Cite
|
Sign up to set email alerts
|

Translational Inhibition of α-Neurexin 2

Abstract: Neurexins are extensively investigated presynaptic cell-adhesion molecules which play important roles in transmitting signals and processing information at synapses that connect neurons into a vast network of cellular communications. Synaptic transmission of information is a fast and dynamic process which relies on rapid and tight regulation of synaptic protein expression. However, the mechanism underlying those regulation is still not fully understood. Therefore, we explore how the expression of NRXN2α, one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Previous work found that multiple conserved, short uORFs within the Nrxn2α 5'UTR cooperatively inhibit translation in vitro (Figure 7-figure supplement 4A) [52]. Interestingly, we find that a longer Nrxn2α uORF using a non-canonical CUG start codon is also translated in developing CPN (Figure 7-figure supplement 4A).…”
Section: Uorf Translation By Cpn: Transcripts Coding For Synaptic And...supporting
confidence: 56%
See 4 more Smart Citations
“…Previous work found that multiple conserved, short uORFs within the Nrxn2α 5'UTR cooperatively inhibit translation in vitro (Figure 7-figure supplement 4A) [52]. Interestingly, we find that a longer Nrxn2α uORF using a non-canonical CUG start codon is also translated in developing CPN (Figure 7-figure supplement 4A).…”
Section: Uorf Translation By Cpn: Transcripts Coding For Synaptic And...supporting
confidence: 56%
“…Interestingly, we find that a longer Nrxn2α uORF using a non-canonical CUG start codon is also translated in developing CPN (Figure 7-figure supplement 4A). While the uORFs identified in the previous study[52] are too short to be directly called by RiboCode, plotting P-site density across these uORFs reveals a bias toward in-frame P-sites across all three uORFs, especially uORF2.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations